Impact of treatment of diabetic macular edema on visual impairment in people with diabetes mellitus in India - Kulkarni, Sucheta (Indian J Ophthalmol, 2021)
PURPOSE: The aim of this study was to report visual and anatomical outcomes following treatment for diabetic macular edema (DME) in clinical practice in India. METHODS: Retrospective chart review of patients with DME who were initiated on treatment and followed up for at least 1 year at 9 tertiary eye care centers during 2016–2017 was performed. Data on demographics, systemic illnesses, visual acuity and anatomical characteristics of DME, treatment history were collated and analyzed for change in visual acuity level and central macular thickness at 1 year. RESULTS: A total 1853 patients were diagnosed with treatable DME during study period, 1315 patients were treated and 556 patients (1019 eyes) followed up at one year. Although patients achieved significantly better anatomical outcome (central macular thickness of <300μ in 32.3% at baseline compared to 60.7% at 1 year, P < 0.001), visual impairment due to DME did not differ from baseline (mild visual impairment in 53.2% at baseline compared to 56% at 1 year, P = 0.7). Cystoid type of DME was the most common phenotype (432/1019, 42.4%) followed by spongy type (325, 31.9%) and cystoid plus spongy type (138, 13.5%). Bevacizumab monotherapy was the most common (388/1019, 38.1%) treatment followed by combination therapy (359, 35.2%). Mean number of anti-VEGF injections received per eye in a year was 2.1 (SD ± 0.9). CONCLUSION: Only about a third of treated DME patients complete one year follow up in India. Most patients receive suboptimal number of treatments. Treated DME cases largely show better anatomical outcome but not a better functional outcome.